Innovation and entrepreneurial opportunities in community tourism - Soares, Jakson Renner Rodrigues, 1980- (Business Science Reference, 2021)
"This book provides relevant theoretical frameworks and the latest empirical research findings in the community tourism for professionals who want to improve their understanding of the innovation in the community tourism network and its contribution to the development of the territory. The relevance of the theme revolves around the dynamic capacities related to small tourism entrepreneurs in the coastal space"--